2013
DOI: 10.4103/0973-1075.110225
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-based classification and physical therapy management of persons with cancer pain: A prospective case series

Abstract: Context:Mechanism-based classification (MBC) was established with current evidence and physical therapy (PT) management methods for both cancer and for noncancer pain.Aims:This study aims to describe the efficacy of MBC-based PT in persons with primary complaints of cancer pain.Settings and Design:A prospective case series of patients who attended the physiotherapy department of a multispecialty university-affiliated teaching hospital.Material and Methods:A total of 24 adults (18 female, 6 male) aged 47.5 ± 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In addition to yoga based exercise intervention, this review identified four physiotherapy based exercise interventions among cancer survivors (Gautam et al 2011 ; Chopra et al 2006 ; Samuel et al 2013 ; Kumar et al 2013 ). Among cancer survivors, the term ‘exercise intervention’ has conventionally been associated with interventions that focus on either or all of aerobic capacity, fitness, muscle strength and endurance, and physical activity; and are usually delivered at a given frequency and intensity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to yoga based exercise intervention, this review identified four physiotherapy based exercise interventions among cancer survivors (Gautam et al 2011 ; Chopra et al 2006 ; Samuel et al 2013 ; Kumar et al 2013 ). Among cancer survivors, the term ‘exercise intervention’ has conventionally been associated with interventions that focus on either or all of aerobic capacity, fitness, muscle strength and endurance, and physical activity; and are usually delivered at a given frequency and intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Although these interventions have been delivered by many healthcare professions (such as physiotherapist s , exercise physiologists, fitness specialists and nurses); the interventions come under the realm of physiotherapy practice and thus we classified them as physiotherapy based interventions. Among the four studies, only one was an RCT (Samuel et al 2013 ), two were single group pre-post intervention design (Gautam et al 2011 ; Chopra et al 2006 ), and one was a case series (Kumar et al 2013 ). The three studies that were eligible for methodological quality rating got a score of 16 (maximum score 32) (Gautam et al 2011 ; Chopra et al 2006 ; Samuel et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patient-centred physical therapy for cancer pain, founded on a mechanisms-based classification of pain, has previously been shown to yield positive findings in a prospective case series. 59 Such mechanism-based pain classification includes the differentiation between nociceptive, neuropathic and central sensitization pain. 56 , 60 Recently, a clinical method for classifying any pain as either predominant central sensitization pain, neuropathic or nociceptive pain 2 was adopted to the cancer survivor population, 61 allowing clinicians to differentiate between these three pain types.…”
Section: Modern Pain Neuroscience Applied To Post-cancer Painmentioning
confidence: 99%
“…For effective pain management, correct identification of the dominant type of pain may be beneficial. Physiotherapy for cancer pain, patient-centered and founded on a mechanisms-based classification of pain, has previously been shown to yield positive findings in a prospective case series [1]. Such mechanism-based pain classification includes the differential classification of nociceptive, neuropathic and central sensitization pain [2,3].…”
mentioning
confidence: 99%